3D-3D facial superimposition between monozygotic twins: A novel morphological approach to the assessment of differences due to environmental factors. (March 2018) - Gibelli, Daniele; Pucciarelli, Valentina; Poppa, Pasquale; De Angelis, Danilo; Cummaudo, Marco; Pisoni, Luca; Codari, Marina; Cattaneo, Cristina; Sforza, Chiarella
Abstract: Distinction of one twin with respect to the other, based on external appearance, is challenging; nevertheless, facial morphology may provide individualizing features that may help distinguish twin siblings. This study aims at exposing an innovative method for the facial assessment in monozygotic twins for personal identification, based on the registration and comparison of 3D models of faces. Ten couples of monozygotic twins aged between 25 and 69 years were acquired twice by a stereophotogrammetric system (VECTRA-3D® M3: Canfield Scientific, Inc., Fairfield, NJ); the 3D reconstruction of each person was then registered and superimposed onto the model belonging to the same person (self-matches), the corresponding sibling (twin-matches) and to unrelated participants from the other couples (miss-matches); RMS (root mean square) point-to-point distances were automatically calculated for all the 220 superimpositions. One-way ANOVA was used to evaluate the differences among miss-matches, twin-matches and self-matches (p < .05). RMS values for self-matches, twin-matches and miss-matches were respectively 1.0 mm (SD: 0.3 mm), 1.9 mm (0.5 mm) and 3.4 mm (0.70 mm). Statistically significant differences were found among the three groups (p < .01). Comparing RMS values in the three groups, mean facial variability in twin siblings was 55.9% of that assessed between unrelated persons and about twice higher than that observed between models belonging to the same individual. The present study proposed an innovative method for the facial assessment of twin siblings, based on 3D surface analysis, which may provide additional information concerning the relation between genes and environment.